2004
DOI: 10.1055/s-2004-830385
|View full text |Cite
|
Sign up to set email alerts
|

Rejuvenation of Ageing Bean Leaves under the Effect of Low‐Dose Stressors

Abstract: The effect of low concentrations of some stress-inducing compounds like Cd, Pb, Ni, and Ti salts and DCMU on the senescence of chloroplasts was investigated in detached primary leaves of bean. After the petioles of ageing leaves had developed roots, these low-dose stressors stimulated chlorophyll synthesis and photosynthetic activity, as compared to the control, thus causing rejuvenation in treated leaves. The amount of photosystem I (lowest in DCMU-treated leaves) and light-harvesting complex II increased, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 54 publications
3
28
0
1
Order By: Relevance
“…Higher starch content might be resulted by the high sucrose concentration of medium but similar transient starch accumulation was observed in planta too as a consequence of stress factors (Nyitrai et al 2004).…”
Section: Discussionmentioning
confidence: 91%
“…Higher starch content might be resulted by the high sucrose concentration of medium but similar transient starch accumulation was observed in planta too as a consequence of stress factors (Nyitrai et al 2004).…”
Section: Discussionmentioning
confidence: 91%
“…It was proposed that Cd in large amounts could replace Zn as a factor favoring the growth of the Zn hyperaccumulator Thlaspi caerulescen (Liu et al 2008). Another possible mechanism for the stimulatory effect of heavy metals may be that metal ions can serve as activators of enzyme(s) in cytokinin metabolism, which accelerates the growth of plants (Nyitrai et al 2004). However, Tang et al (2009) assumed that the stimulatory response of plants to heavy metals may be a rare and extreme phenomenon of hormesis, and the physiological metabolisms of plants may respond differently to the heavy metals at the stimulatory and inhibitory dose range.…”
Section: Discussionmentioning
confidence: 98%
“…An impossible mechanism for the stimulatory effect of Cd may be that metal ions can serve as activators of enzyme(s) in cytokinin metabolism, which accelerates the growth of plants. It was reported that cytokinins can delay senescence while maintaining the chlorophyll and photosynthetic activity of leaf tissues [38] and can take part in the remediation of the effect of some low-dose heavy metals [39]. However, a sharp reduction in cytokinin content in wheat seedlings (Triticum durum) was observed within 2 h of supplying cadmium [40].…”
Section: Shoot Biomass Response To Soil CD Toxicitymentioning
confidence: 99%